Synchrotron X-ray characterisation of crack strain fields in polygranular graphite - Barhli, S; Saucedo-Mora, L; Jordan, M; Cinar, A; Reinhard, C; Mostafavi, M; Marrow, T (Elsevier, 2017)
The strain field of a crack in polygranular isotropic nuclear graphite, a quasi-brittle material, has been studied during stable fracture propagation. Synchrotron X-ray computed tomography and strain mapping by diffraction were combined with digital volume correlation and phase congruency image analysis to extract the full field displacements and elastic crystal strains. The measured displacement fields have been analysed using a Finite Element method to extract the elastic strain energy release rate as a J-integral. Non-linear properties described the effect of microcracking on the elastic modulus in the fracture process zone. The analysis was verified by the good agreement of the predicted and measured elastic strain fields when using the non-linear model. The intrinsic critical elastic strain energy release rate for mode I crack propagation is approximately 200 J m-2 .